THE ASIA FOUNDATION ROLES IN MYANMAR CONSOLIDATION OF DEMOCRACY AFTER TRANSITION ERA - Rayhana Fajria (HI 15 UMY 289, 2015)
*289 Before the transition era, Myanmar had been experiencing various kind of problems in its governmental system which disrepute led onto almost of all aspects within the society. The intervention of the military began. In the 1960, elections were done well, and U Nu with his party, the Union Party, got the winning back. Due to a lot of economic problems in the country, military government gave certain ultimatums toward the civil administration for about 2 years to solve them all. Yet, U Nu government was failed to improve the condition in the country, until 1962 General Ne Win led a coup d'Ã©tat and established a nominally socialist military government. All the poor systems and suffering were started here. The military expropriated private businesses and followed an economic policy of autarky, or economic isolation. The quality of economy, law, social, the culture diversity, and political freedom, were decreasing during the military authority.